A novel hematopoietic progenitor cell mobilization and collection algorithm based on preemptive CD34 enumeration. Issue 8 (21st March 2015) - Storch, Emily; Mark, Tomer; Avecilla, Scott; Pagan, Carlos; Rhodes, Joanna; Shore, Tsiporah; van Besien, Koen; Cushing, Melissa
<x xml:space="preserve">Abstract</x> BACKGROUND The collection of autologous peripheral blood (PB) stem cells can be challenging in the subgroup of patients deemed "poor mobilizers" with granulocyte–colony‐stimulating factor. Plerixafor, a CXCR‐4 antagonist, is an alternative mobilizing agent, but is costly, and the optimal mobilization algorithm has yet to be determined. STUDY DESIGN AND METHODS To address the question we developed a protocol measuring PB CD34 on Day 4 of mobilization. We examined 26 patients before initiating the protocol versus 24 patients after initiation. RESULTS Significant differences (p ≤ 0.05) included fewer days of collection (1.25 days vs. 2.42 days), lower total blood volume processed (25.9 L vs. 57.2 L), lower total product volume (324 mL vs. 691 mL), lower RBC content (9 mL vs. 18 mL), and lower granulocyte percentage per collection (35% vs. 11%). There were no significant differences between the two groups in demographics, baseline platelet count, total CD34, or CD34/kg harvested. CONCLUSION Use of a protocol to assess PB CD34 1 day before collection allows for preemptive administration of plerixafor to augment mobilization. Subsequently, days of collection and processed blood volume are reduced while there is less RBC and granulocyte contamination in the collected stem cell product.